Funerary posts and Christian crosses: Fataluku cohabitations with Catholic missionaries after world war II (Timor-Leste) - Viegas, Susana de Matos (2019)
One day, in the village of Laiara, located in the easternmost Timorese district of Lautem, where the Fataluku speakers reside, we entered a house built on high wooden pillars; behind it were the graves of several of its deceased residents. which we later visited. We had come to talk with a group of six men about Nari. a locality situated on a nearby plateau six hundred meters above sea leve. All those men were patrilineal descendants of the central figure in a book authored by the Salesian missionary José Bernardino Rodrigues. ln that book. Father Rodrigues describes his relationships with Fataluku speakers in Lautem between 1947 and 1957. referring specifically to his personal relationship with a man named Perekoro. whom he called "the king of Nari."